International and regional mechanisms for the protection of property rights (Journal of actual problems of jurisprudence, 2018)
Protection of property rights is a key priority of any rule of law. Ownership in modern legal literature is treated as an institution of civil society, the private Institute for fundamental rights and recognized universal value. The article deals with the problem of development of the concept of property rights, analyzed international standards of legal regulation of property rights, regional mechanisms for the protection of property rights.In the modern period of development of the relevant international legal institution of protection of property rights in the twofold way – as an institution of international human rights and as a factor in the modernization of the National Institute of ownership.Key words: law, property, regional mechanisms, remedies.